1998
DOI: 10.1038/sj.bjp.0701847
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in the signalling cascade of cyclosporine A‐mediated up‐regulation of eNOS in vascular endothelial cells

Abstract: 1. Cyclosporine A (CsA) increases eNOS mRNA expression in bovine cultured aortic endothelial cells (BAEC). As some effects of CsA may be mediated by reactive oxygen species (ROS), present experiments were devoted to test the hypothesis that the CsA-induced eNOS up-regulation could be dependent on an increased synthesis of ROS. 2. CsA induced a dose-dependent increase of ROS synthesis, with the two fluorescent probes used, DHR123 (CsA 1 microM: 305+/-7% over control) and H2DCFDA (CsA 1 microM: 178+/-6% over con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…Drummond et al (35) recently reported that treatment of aortic endothelial cells with H 2 O 2 resulted in increased expression of eNOS protein at the transcriptional level after 18 -24 h, and this increased protein expression resulted in enhanced NO bioactivity. Reactive oxygen species have also been reported to account for the ability of long term cyclosporin A treatment to stimulate eNOS mRNA and protein expression in aortic endothelial cells (36). In the current study, we examined the short term implications of H 2 O 2 on eNOS activity in PAECs.…”
Section: Discussionmentioning
confidence: 99%
“…Drummond et al (35) recently reported that treatment of aortic endothelial cells with H 2 O 2 resulted in increased expression of eNOS protein at the transcriptional level after 18 -24 h, and this increased protein expression resulted in enhanced NO bioactivity. Reactive oxygen species have also been reported to account for the ability of long term cyclosporin A treatment to stimulate eNOS mRNA and protein expression in aortic endothelial cells (36). In the current study, we examined the short term implications of H 2 O 2 on eNOS activity in PAECs.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike inducible genes, that are transcribed only when they are needed as a consequence of specific stimuli, constitutive genes are expressed continuously in cells, and it seems that they play significant roles in the maintenance of basic cell processes. Although the transcription level of constitutive genes seems to be rather constant, it has been reported that they can be also regulated by different stimuli, such as reactive oxygen species (ROS) (7,12,18,27,43). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, ethanol, as a small exogenous liposoluble molecule, can be metabolized by mitochondrial enzyme systems, accompanied by reactive oxygen species (ROS) generation. ROS have detrimental or beneficial effects on eNOS activation depending on its concentrations [5,6]. During ethanol exposure, ROS level is dependent on the capability of antioxidant systems to antagonize ROS generation.…”
Section: Introductionmentioning
confidence: 99%